Loose architectural fragments - Temples of India Project Team (Jio Institute, 2024)
It is likely that the beam, richly carved with human figures, adorned the varandika of the temple, the adjoining portions between the temple walls and the spire. The protruding offsets typically contain mithuna figures inside the niches, while the recesses between the two offsets are beautifully carved with images of apsaras.